2022
DOI: 10.5937/gp26-35582
|View full text |Cite
|
Sign up to set email alerts
|

A community-based approach to mainstream human-nature interactions into coastal risk governance: A case of Katrenikona, India

Abstract: Coastal rural communities, being intricately associated with their ecological settings, are often highly vulnerable to climate change. Amongst the many approaches of reducing the coastal vulnerabilities and achieving climate change adaptation, a potential solution is to improve risk governance through integrated coastal zone management. The coastal risk governance signifies not only the actions of the state but also of other stakeholders, especially the local communities. Community-based approaches have also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The lens of human-nature interactions supports unlocking the hidden but rapidly changing components of the coastal SES [17], which is partly in the hands of local communities and their choices [72]. It was found that despite the existing illiteracy, remoteness, and technological and economic hurdles in the region, the FCM method proves to be effective for accumulating all previous experiences as well as the present knowledge of local communities regarding the SES of the study area.…”
Section: Community Participationmentioning
confidence: 95%
See 1 more Smart Citation
“…The lens of human-nature interactions supports unlocking the hidden but rapidly changing components of the coastal SES [17], which is partly in the hands of local communities and their choices [72]. It was found that despite the existing illiteracy, remoteness, and technological and economic hurdles in the region, the FCM method proves to be effective for accumulating all previous experiences as well as the present knowledge of local communities regarding the SES of the study area.…”
Section: Community Participationmentioning
confidence: 95%
“…Many global reports-for instance, the Sendai framework for disaster risk reduction, the IPCC SROC 2019 report, and others [4]-have stressed the important role of communities in improving disaster risk decision-making and unraveling the complexity and dynamic nature of SES. Although the importance of uncertainty is highlighted in many studies [17], only a few of these prioritize the uncertainty generated by individual influence [18], policy decisions [19], and sustainability at the global level. As a result, it is difficult to forecast how disaster-related policies will affect the future path of resilience and sustainability, especially in complex and dynamic SESs such as coastal rural systems.…”
Section: Introductionmentioning
confidence: 99%